2018
DOI: 10.1152/ajpcell.00024.2017
|View full text |Cite
|
Sign up to set email alerts
|

Adenosinergic signaling inhibits oxalate transport by human intestinal Caco2-BBE cells through the A2B adenosine receptor

Abstract: Most kidney stones (KS) are composed of calcium oxalate, and small increases in urine oxalate affect the stone risk. Intestinal oxalate secretion mediated by anion exchanger SLC26A6 (PAT1) plays a crucial role in limiting net absorption of ingested oxalate; thereby preventing hyperoxaluria and related KS, reflecting the importance of understanding regulation of intestinal oxalate transport. We previously showed that ATP and UTP inhibit oxalate transport by human intestinal Caco2-BBE cells (C2). Since ATP is ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…To complement the knowledge obtained from individual pathway prioritizations, we next exploited interaction information merged from all KEGG pathways to identify a pathway crosstalk that contains highly ranked and interconnecting genes ( p =3.2×10 −99 on permutation test; Figure 3A and Table S4 ). Genes in this crosstalk include those previously reported to be of functional relevance to nephrolithiasis, such as protein kinase C ( PRKCA , PRKCB , and PRKCZ ) ( 43 ), markers ( CD40 and TLR3 ) ( 44 ), and autophagy ( MTOR and SQSTM1 ) ( 13 ), thus validating our genetic prioritization at the gene and pathway level. Based on pathways significantly over-represented in the crosstalk ( Figure S5 ), we further constructed crosstalk at the pathway level, with edges estimated by the extent to which member genes are shared between two endpoints ( Figure 3B ).…”
Section: Resultssupporting
confidence: 72%
“…To complement the knowledge obtained from individual pathway prioritizations, we next exploited interaction information merged from all KEGG pathways to identify a pathway crosstalk that contains highly ranked and interconnecting genes ( p =3.2×10 −99 on permutation test; Figure 3A and Table S4 ). Genes in this crosstalk include those previously reported to be of functional relevance to nephrolithiasis, such as protein kinase C ( PRKCA , PRKCB , and PRKCZ ) ( 43 ), markers ( CD40 and TLR3 ) ( 44 ), and autophagy ( MTOR and SQSTM1 ) ( 13 ), thus validating our genetic prioritization at the gene and pathway level. Based on pathways significantly over-represented in the crosstalk ( Figure S5 ), we further constructed crosstalk at the pathway level, with edges estimated by the extent to which member genes are shared between two endpoints ( Figure 3B ).…”
Section: Resultssupporting
confidence: 72%
“…To ensure that the stimulatory regulation of intestinal oxalate transport by the PKA signaling pathway is not cell line specific, we similarly evaluated the effects of F/I on oxalate uptake by the human colonic cell line T84. Of note is that we (5,20,28) had previously established T84 cells as a useful model to study regulation of intestinal oxalate transport by cholinergic and adenosinergic signaling, as well as by Oxalobacter-derived secreted factors. We (20) had also shown that A6 mediates most of oxalate transport in T84 cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, A6 can operate in either direction (27), and we therefore measured its activity by the more convenient assay of cellular oxalate uptake. Worthy of mention is that we (4,5,28) had previously established C2 cells as a useful model to study the regulation of intestinal oxalate transport by purinergic and adenosinergic signaling, as well as by Oxalobacter-derived secreted bioactive factors.…”
Section: Introductionmentioning
confidence: 99%
“…Cholinergic regulation inhibits oxalate uptake through reduced expression of SCL26A6 in human cell lines (8)(9)(10). A purinergic signaling system also regulates J o u r n a l P r e -p r o o f oxalate transport across digestive epithelia (11)(12). Lastly, in murine chronic kidney disease (CKD) models, Slc26a6-mediated enteric oxalate secretion is critical in decreasing the body burden of oxalate (13).…”
Section: Oxalate Metabolism and Measurementmentioning
confidence: 99%